1997
DOI: 10.1139/cjfas-54-s1-68
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydrography and circulation on the Newfoundland Shelf during Pages 1990–1993 with the long-term mean

Abstract: Meteorological and ice data from the Atlantic region indicate that the large-scale atmospheric circulation over the Northwest Atlantic during the early 1990s caused below-normal air temperatures in eastern Canada, resulting in increased ice growth during winter, increased ice transport from northern latitudes, and increased freshwater from melting ice during spring. The reduced solar flux onto the ocean surface resulted in a 3-to 4-wk delay in the annual warming cycle causing record low temperatures over the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 22 publications
2
37
1
Order By: Relevance
“…The spatial amplitude S 1 has similar vertical distributions for temperature and salinity anomalies at transect AA ′ , featuring relatively larger values in the top 200 m and smaller values in the lower layer of the transect, with a maximum at about 40 m over the shelf break of the transect. Colbourne et al (1997) revealed an intense southward jet in the top 100 m at Seal Island close to transect AA ′ . This suggests that the southward advection of the interannual variability carried by the offshore branch of the Labrador Current is responsible for the maximum interannual variability in the monthly mean temperature and salinity in the upper layer of the transect shown in Fig.…”
Section: B the Complex Empirical Orthogonal Function Analysismentioning
confidence: 98%
See 3 more Smart Citations
“…The spatial amplitude S 1 has similar vertical distributions for temperature and salinity anomalies at transect AA ′ , featuring relatively larger values in the top 200 m and smaller values in the lower layer of the transect, with a maximum at about 40 m over the shelf break of the transect. Colbourne et al (1997) revealed an intense southward jet in the top 100 m at Seal Island close to transect AA ′ . This suggests that the southward advection of the interannual variability carried by the offshore branch of the Labrador Current is responsible for the maximum interannual variability in the monthly mean temperature and salinity in the upper layer of the transect shown in Fig.…”
Section: B the Complex Empirical Orthogonal Function Analysismentioning
confidence: 98%
“…The rest of the inner branch and the other two branches flow onto the Newfoundland Shelf. Over the northern Newfoundland Shelf, the Labrador Current has a coastal branch flowing through Avalon Channel to the coastal waters of southern Newfoundland, a middle branch following the shelf break through Flemish Pass, and an eastern branch passing around the seaward flank of Flemish Cap (Petrie and Anderson, 1983;Sheng and Thompson, 1996;Colbourne et al, 1997;Loder et al, 1998;Han et al, 2008). Part of the eastern branch of the Labrador Current over the northern Newfoundland Shelf moves into the deep ocean to join the North Atlantic Current, and the rest joins the middle branch to the south of the Flemish Pass (Han et al, 2008).…”
Section: Review Of Circulation and Hydrographic Features On The Eastementioning
confidence: 99%
See 2 more Smart Citations
“…The ocean circulation in the Northwest Atlantic has been described many times (Smith et al, 1937;Peterson, 1987;Greenberg and Petrie, 1988;Chapman and Beardsley, 1989;Lazier and Wright 1993;Petrie and Anderson, 1983;Drinkwater, 1996 andColbourne et al, 1997a). The following brief discussion summarizes the main ocean current features influencing the Newfoundland and Labrador Shelf region.…”
Section: Introductionmentioning
confidence: 96%